Cost-effectiveness analysis of the treatment of posttraumatic stress disorder related to childhood abuse: comparison of phase-based treatment and direct trauma-focused treatment - van Vliet, Noortje I.; Stant, A. Dennis; Huntjens, Rafaele; van Dijk, Maarten K.; de Jongh, Ad (Frontiers in Psychology, 2024)
Background Policymakers, health insurers, and health care providers are becoming increasingly interested in cost-effectiveness analyses (CEA’s) when choosing between possible treatment alternatives, as costs for mental health care have been increasing in recent years. Objective The current study compared the cost-effectiveness and cost-utility of a phased-based treatment approach that included a preparatory stabilization phase with direct trauma-focused treatment in patients with PTSD and a history of childhood abuse. Method A cost-effectiveness analysis was conducted based on data from a randomized controlled trial of 121 patients with PTSD due to childhood abuse. A phase-based treatment (Eye Movement Desensitization and Reprocessing [EMDR] therapy preceded by Skills Training in Affect and Interpersonal Regulation [STAIR]; n = 57) was compared with a direct trauma-focused treatment (EMDR therapy only; n = 64). The primary outcome of cost-effectiveness was the proportion of patients with remitted PTSD. Quality-adjusted life years (QALY) were used as the primary outcome measure for cost-utility analysis. Results Although the results of the cost-effectiveness analyses yielded no statistically significant differences between the two groups, the mean societal costs per patient differed significantly between the STAIR-EMDR and EMDR therapy groups (€19.599 vs. €13.501; M cost differences = €6.098, CI (95%) = [€117 ; €12.644]). Conclusions STAIR-EMDR is not cost-effective compared with EMDR-only therapy. Since trauma-focused treatment is less time-consuming, non-trauma-focused phase-based, treatment does not seem to be a viable alternative for the treatment of PTSD due to adverse childhood events.